Transformational leadership, Personality, and Job Satisfactionin shaping Organizational Citizenship Behavior : Kepemimpinan Transformasional, Personality dan Kepuasan Kerja dalam membentuk Organizational Citizenship Behavior - Fidy Famerta; Rifdah Abadiyah (Academia Open, 2022)
This study aims to determine the effect of Transformational Leadership (X1), Personality (X2) and Job Satisfaction (X3) on Organizational Citizenship Behavior (Y). In this study using quantitative methods, namely research methods in the form of numbers and analysis using statistics. The sample for this study was 132 employees. In this sampling technique using non-probability sampling technique. The results of this study indicate that Transformational Leadership partially positive effect on Organizational Citizenship Behavior, Personality partially positive effect on Organizational Citizenship Behavior, Job Satisfaction partially positive effect on Organizational Citizenship Behavior. Highlights: Transformational Leadership positively influences Organizational Citizenship Behavior. Personality has a positive impact on Organizational Citizenship Behavior. Job Satisfaction is associated with increased Organizational Citizenship Behavior. Keywords: Transformational Leadership, Personality, Job Satisfaction, Organizational Citizenship Behavior.